Gestión publicitaria implementada por las empresas de publicidad y su incidencia en la aceptación de los usuarios de la ciudad de Quevedo, año 2016 - Lucas Choez, José Jonathan (2016)
The research entitled Advertising Management implemented by Advertising Companies and its impact on the Acceptance of Users of the city of Quevedo, in 2016, aims to analyze the advertising management implemented by advertising companies and the acceptance of users; Identify the companies dedicated to providing the advertising service in the city; Describe the communication strategies applied by the companies offering the advertising service; To interpret the degree of recognition that the users who use the advertising services that the agencies of the Canton offer and to design an advertising proposal that contributes to the promotion of the services demanded by the users of the canton Quevedo to the company with less recognition. We applied the types of field and bibliographic research, the methods used are inductive, deductive and analytical, the population consisted of an average of 200 clients by agencies that exist in the canton. According to data from the Municipal GAD of Quevedo, 23 Advertising Agencies are registered, with a total of 4600 clients. Obtaining the following results: The companies that offer the advertising service do not apply innovative strategies that boost the commercial growth of their business, nor do they offer promotions that allow the loyalty of users who require their services, in addition, it is established that Agencia JC Publicidad presents Major disadvantages have a low average customer generated by the limited application of advertising and promotion strategies. Proposing as a recommendation to offer advertising services that diversify the range of products and services such as online marketing, direct, digital, branding and cobranding among others, to help meet the needs of customers.